Analisis determinan ketersediaan dokter spesialis dan gambaran fasilitas kesehatan di RSU pemerintah kabupaten/kota Indonesia (analisis data rifaskes 2011) - Heri Priyatmoko; Lutfan Lazuardi; Mubasysyir Hasanbasri (Center for Health Policy and Management, 2014)
Determinants of specialist availability in public hospitals: analysis of 2011 RifaskesABSTRACT Background:Indonesia still faces theproblem of unequal distribution of specialist doctors. The ratio of health workers per 100.000 population has not met the target. In 2008, the ratio of health workers to medical specialist per 100.000 population amounted to 7,73 compared to the target which is 9. Some areas of development in underserved areas, such as low economic power, lack of hospital system capacity and hospital medical equipment, have been neglected by government. Engagement of stakeholder to improve hospital quality system is a critical element to contribute to the policy of specialist doctors dsitribution, typically to increase the number of specialist doctors practising in rural and remote areas. Objective: To assess the determinants ofavailability of specialist doctors in government/public hospitals and to find out the correlation of variable factors. Methods: A cross sectional design was adopted for this study, in which 7 factors were chosen to assess determinant of availability of specialist doctors using a Health Facilities Research (Rifaskes) conducted Bay the HealthMinistry in 2011 and to describe availibility of hospital facilities in the Indonesian public hospitals. Results: Bivariate analysis indicated that level of district, hospital accredited, BLU versus Non-BLU, remuneration, hospital facilities, dan GNP significantly affect to the number of specialist doctors (p <0,05). Logistic regression indicated that the strongest predictors of availibility specialist is accredited public hospital with 12 standard of care (odds ratio 9,32 ; 95% CI: 1,2-72,4) ; p < 0.03). Level of district have significantly associated to availibility specialist in public hospital (odds ratio 2,15 ; (95% CI: 1,36-3,39) ; p = 0,001). Conclusion: The current study makes an important contribution to the literature in finding the determinants of distribution of specialist doctors in public hospital in Indonesia to address maldistribution between urban and rural barriers. Additional research is needed to examine preference to choose rural location and the incorporation of other retention strategies, such as medical educationinitiatives, community and professional support, differential rural fees and alternate funding models. Keywords: Availability,specialist doctors, specialistic facilities